Analysis of the effects of digital transformation of enterprise clusters on innovation performance in the context of “Internet+” - Sumei Zeng; Jinding Bao (Systems and Soft Computing)
With the rapid development of digital economy, the social process of ''Internet+'' has accelerated. The digital transformation of enterprise clusters has now become one of the key strategy to enhance the competitiveness and innovation ability of enterprises. A comprehensive and accurate analysis of the impact of digital transformation on the innovation performance of enterprises has a crucial impact on improving the economic benefits of enterprises. However, at present, the analysis of the innovation performance of digital transformation is not sufficient, and there are some limitations and one-sided points. Therefore, the research puts forward the impact model of the digital transformation of enterprise cluster based on cross-level analysis. The influence of the mechanism of enterprise cluster cooperation atmosphere on enterprise innovation performance is analyzed. The results of regression analysis show that the positive impact factor of enterprise cluster cooperation atmosphere on enterprise efficiency is enterprises (P < 0.05). To summarize the findings, both the collaborative environment and the identification of enterprise clusters have a significant positive impact on enterprise efficiency (P < 0.01). When the cooperation atmosphere within the enterprise cluster is good and the enterprise cluster members have a strong sense of identification to the cluster, the innovation performance and efficiency of the enterprise will be significantly improved. The research results reveal the influence of enterprise clusters on innovation performance, and provide a reference theory for the digital transformation of enterprise clusters in other regions.